Response of the underground environment of the KAGRA observatory against the air pressure disturbance from the Tonga volcanic eruption on January 15, 2022. (19th September 2022) - Washimi, Tatsuki; Yokozawa, Takaaki; Takamori, Akiteru; Araya, Akito; Hoshino, Sota; Itoh, Yousuke; Kobayashi, Yuichiro; Kume, Jun'ya; Miyo, Kouseki; Ohkawa, Masashi; Oshino, Shoichi; Tomaru, Takayuki; et al.
Abstract: On January 15, 2022, at 04:14:45 (UTC), the Hunga Tonga-Funga Ha'apai, a submarine volcano in the Tongan archipelago in the southern Pacific Ocean, erupted and generated global seismic, shock, and electromagnetic waves, which also reached Japan, situated more than 8000 km away. KAGRA is a gravitational wave telescope located in an underground facility in Kamioka, Japan. It has a wide variety of auxiliary sensors to monitor environmental disturbances that obstruct the observation of gravitational waves. The effects of the volcanic eruption were observed by these environmental sensors both inside and outside of the underground facility. In particular, the shock waves made it possible to evaluate the transfer functions from the air pressure wave in the atmosphere to the underground environmental disturbances (air pressure and seismic motion).